Kedudukan Tanah Harato Pusako Tinggi yang Berbatasan dengan Tanah Timbul (Pasie Maelo) Ditinjau Berdasarkan Hukum Pertanahan (Studi Kasus Putusan Nomor 55/Pdt.G/2022/PN.Pmn) - Fathin Fidia Notarisya (CV Rewang Rencang, 2025)
This research is based on the background of a dispute over overlapping ownership between customary law community as the holder of tanah harato pusako tinggi and the Government as the holder of Aanslibbing in the application for registration of land rights, which occurred in the coastal area of Pariaman City. This research aims to identify control of Aanslibbing due to shifts in coastlines based on land law and to analyzed the position of tanah harato pusako tinggi as Customary Law Community’s Rights that borders the Aanslibbing in Case No. 55/Pdt.G/2022/Pn. Pmn. The research is explanatory, qualitatively evaluated, and employs a doctrinal approach based on secondary data. The study's findings demonstrate that the management of Aanslibbing is done in compliance with its terms, allowing the state to hold it, or in accordance with previous rights and the public interest concept. The Contradictoire Delimitatie Principle must serve as the foundation for the control and release of Aanslibbing. Additionally, the study discovered that the Plaintiffs are acknowledged and protected as a community governed by customary law, and that the Harato Pusako Tinggi land is customary land. Thus, the position of tanah harato pusako tinggi is recognized and cannot be claimed without the consent of the customary law community that owns it.